A Quantitative Bacteria Monitoring and Killing Platform Based on Electron Transfer from Bacteria to a Semiconductor. Issue 39 (19th August 2020) - Wang, Guomin; Tang, Kaiwei; Meng, Zheyi; Liu, Pei; Mo, Shi; Mehrjou, Babak; Wang, Huaiyu; Liu, Xuanyong; Wu, Zhengwei; Chu, Paul K.
Abstract: A platform with both bacteria killing and sensing capabilities is crucial for monitoring the entire bacteria‐related process on biomaterials and biomedical devices. Electron transfer (ET) between the bacteria and a Au‐loaded semiconductor (ZnO) is observed to be the primary factor for effective bacteria sensing and fast bacteria killing. The electrons produce a saturation current that varies linearly with the bacteria number, semi‐logarithmically, with R 2 of 0.98825, thus providing an excellent tool to count bacteria quantitatively in real‐time. Furthermore, ET leads to continuous electron loss killing of about 80% of Escherichia coli in only 1 h without light. The modularity and extendability of this ET‐based platform are also demonstrated by the excellent results obtained from other semiconductor/substrate systems and the stability is confirmed by recycling tests. The underlying mechanism for the dual functions is not due to conventional attributed Zn 2+ leaching or photocatalysis but instead electrical interactions upon direct contact. The results reveal the capability of real‐time detection of bacteria based on ET while providing information about the antibacterial behavior of ZnO‐based materials especially in the early stage. The concept can be readily incorporated into the design of smart and miniaturized devices that can sense and kill bacteria simultaneously. Abstract : Enhanced electron transfer (ET) from bacteria to a Au‐modified semiconductor (Au@ZnO) is observed for fast bacteria sensing and killing with excellent extendability, stability, and recyclability. ET produces a saturation current depending linearly on the bacterial number, semi‐logarithmically, and continuous electron loss swiftly kills bacteria. The concept can be incorporated into smart and miniaturized devices that sense and kill bacteria simultaneously.